(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Social commerce revolutionized the marketing of accommodations through online campaigns, social media promotions, and development of landing pages. Marketing, at its core, induced the customers to buy the products, while the establishment of the internet shaped different marketing strategies. The aim of this study was to develop a consumer-centered analysis that focused on their initial perception on accommodation products in a marketing campaign. This exploratory study analyzed the narratives of 8 customers who availed accommodation through a marketing campaign. Content analysis revealed that the most appealing marketing characteristic for customers was the social media presence, which showed the information customers need convincing them to purchase the products. Promoting price points and location were also remarkable for customers. The customers thought that presentation-wise, location and prices enabled them to make a purchasing decision. These characteristics allowed them to compare and visualize its differences to services offered by other accommodations. Other components such as convenience, security, and cleanliness also had notable influence on customer purchase intention. The results in this study offered new opportunity to hoteliers and hospitality industry to develop a marketing set up that uses targeted promotion and quality highlighting. These results constructed new perspectives on how to approach marketing and management in a competitive scale.